2024
DOI: 10.1186/s12889-024-18099-4
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national burden of non-communicable diseases attributable to occupational asbestos exposure 1990–2019 and prediction to 2035: worsening or improving?

Xinlu Miao,
Teng Yao,
Chenxian Dong
et al.

Abstract: Understanding the burden associated with occupational asbestos exposure on a global and regional scale is necessary to implement coordinated prevention and control strategies. By the GBD Study 2019, we conducted a comprehensive assessment of the non-communicable diseases burden attributable to occupational asbestos exposure. In 2019, 239,330 deaths and 4,189,000 disability-adjusted life years (DALYs) worldwide due to occupational asbestos exposure occurred. 1990–2019, deaths and DALYs attributed to occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…All forms of asbestos are pathogenic (World Health Organization 2014 ) to humans and may cause diseases such as pulmonary fibrosis (Wilk and Krowczynska 2021 ), cancer (Straif et al 2009 ), (Institute of Medicine Committee on Asbestos and Selected Health Effects 2006 ; Wronkiewicz et al 2020 ; Acheson et al 1982 ; Kim et al 2024 ) especially cancer of the respiratory system (Henderson and Enterline 1979 ; Kwak et al 2022 ). A GBD study showed that global deaths attributable to occupational asbestos exposure will increase by 2035 (Miao et al 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…All forms of asbestos are pathogenic (World Health Organization 2014 ) to humans and may cause diseases such as pulmonary fibrosis (Wilk and Krowczynska 2021 ), cancer (Straif et al 2009 ), (Institute of Medicine Committee on Asbestos and Selected Health Effects 2006 ; Wronkiewicz et al 2020 ; Acheson et al 1982 ; Kim et al 2024 ) especially cancer of the respiratory system (Henderson and Enterline 1979 ; Kwak et al 2022 ). A GBD study showed that global deaths attributable to occupational asbestos exposure will increase by 2035 (Miao et al 2024 ).…”
Section: Introductionmentioning
confidence: 99%